Contextualization in theological endeavor - Cervera Conte SJ, Ignacio (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
From the sixties onward, much literature has been produced on the topic of «contextualization» and «contextual theology». More than another theology, contextual theology should be described as the effort of theology to be of relevance in its own context. Several trends, such as «indigenization», «inculturation», «localization», share the same purpose. This paper tries to explain the terminology used by the authors, and to give some criteria both to identify contexts and to evaluate the different models of contextualization.